Biological Dosimetry Network in Africa: Establishment of a Dose-Response Curve Using Telomere and Centromere Staining. Issue 6 (December 2019) - Soumboundou, Mamadou; Nkengurutse, Innocent; Dossou, Julien; Colicchio, Bruno; Djebou, Catherine; Gadji, Macoura; Houenon, Germain; Dem, Ahmadou; Dedjan, Alexandre; Diarra, Mounibé; Adjibade, Rachad; Finot, Francis; et al.
Abstract : Abstract: Purpose: Biological dosimetry, based on the relationship between the absorbed dose after exposure to ionizing radiation and the frequency of scored aberrations, has been and continues to be an important tool for estimating the dose after exposure. Dicentric chromosomes are considered to be the most specific and sensitive aberration related to radiation exposure. Here, we established the dose-response curve following in vitro irradiation of circulating lymphocytes from healthy donors from three African countries after scoring unstable chromosomal aberrations. Materials and methods: Blood samples from 16 African donors were exposed to various doses (0 to 4 Gy) using an X-RAD320 x-ray system with a maximum photon energy of 250 kV at a dose rate of 0.1 Gy min −1 . Blood lymphocytes were cultured for 48 h, and chromosomal aberrations were scored during the first mitosis by telomere and centromere staining. The distribution of dicentric chromosomes was determined . Results: No dicentric chromosomes were found after the analysis of 2, 669 first-division metaphases before in vitro exposure. We established a linear-quadratic dose-response curve based on the frequency of dicentric and ring chromosomes and calculated double-strand breaks, taking into account all scored aberrations. Conclusion: The generation of a specific dose-response curve for African donors will allow the practice of precise biological dosimetry in these countries. This work is the first step towards realizing an African biodosimetry network and the establishment of a biological dosimetry laboratory, which could play a major role in the application of radioprotection norms.